Comparative outcome assessment of total hip arthroplasty versus bipolar hemiarthroplasty in intracapsular neck of femur fracture in old age - Muslim, Sufyan M.; Lingayat, M. B.; Bansode, Prashant; Kesharwani, Arpit (International Journal of Research in Orthopaedics, 2023)
Background: This prospective study aimed to compare the outcomes of total hip replacement (THR) and bipolar hemiarthroplasty for the treatment of displaced femoral neck fractures in elderly patients. Methods: A total of 30 patients aged over 60 years with femoral neck fractures were included in the study, with 15 patients receiving a bipolar prosthesis and patients receiving THR between June 2021 and January 2023. The patients were followed up for 6 months postoperatively, with functional analysis conducted using the modified Harris hip score. Results: The results showed that the modified Harris hip score was significantly higher in the THR group compared to the bipolar prosthesis group at day 1, 3, 6 and 12 months postoperatively. Pain levels were similar between the two groups at all follow-up intervals. Gait and range of motion were significantly higher in the THR group compared to the bipolar prosthesis group at all-time points. Conclusions: Based on the short-term functional outcomes of this study, THR appears to be a preferable option over bipolar prosthesis for managing femoral neck fractures in elderly.